Peran Kepemimpinan Kepala Sekolah Dalam Meningkatkan Mutu Lulusan - Aan Suryanto; Tri Yuni Hendrowati; M. Badrun (Manajemen Pendidikan, 2025)
This research examines the role of school leadership in improving the quality of graduates in vocationalhigh schools (SMK). The focus of this research is how the effective leadership of a principal caninfluence the quality of education and student learning outcomes. This study employs a qualitativeapproach using a case study method at a vocational high school in Indonesia. Data were collectedthrough in-depth interviews, observations, and analysis of school documents. The findings revealthat principals who have a clear vision, strong managerial skills, and the ability to motivate andinspire both teachers and students can significantly enhance the quality of graduates. Furthermore,collaborative and participatory leadership is also proven to be crucial in creating a conducive andinnovative learning environment. These findings highlight the importance of adaptive and proactiveleadership in addressing the challenges of education in the era of globalization.